2020
DOI: 10.1016/j.ejvs.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Results of the French EPI-ANA-01 Registry of AnacondaTM Endografts in the Treatment of Infrarenal Abdominal Aortic Aneurysms

Abstract: WHAT THIS PAPER ADDSThis observational prospective multicentre series reports the longest term results of the third generation Anaconda device in infrarenal aortic aneurysms with good data consistency. The endograft provided high technical success. During this five year assessment, secondary interventions were performed in 35 of 176 patients (19.9%) and a significant aneurysm diameter decrease of À13.5% was observed, yet the limb occlusion rate remained high (15 limbs [4.3%] in 14 patients [7.9%]) and was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 39 publications
(42 reference statements)
1
22
1
Order By: Relevance
“…17 Most of the reported experience with the Anaconda™ endograft comes from secondgeneration devices. 15,16,24,25 Only one reported study has included only third-generation devices 23 and a few studies included mixed populations. 7,13,14,17 Rödel et al included both second-and third-generation grafts and reported an overall occlusion rate of 9.8% over a mean follow-up of 47 months, with no difference in occlusion between second-and third-generation grafts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Most of the reported experience with the Anaconda™ endograft comes from secondgeneration devices. 15,16,24,25 Only one reported study has included only third-generation devices 23 and a few studies included mixed populations. 7,13,14,17 Rödel et al included both second-and third-generation grafts and reported an overall occlusion rate of 9.8% over a mean follow-up of 47 months, with no difference in occlusion between second-and third-generation grafts.…”
Section: Discussionmentioning
confidence: 99%
“…al found an occlusion rate of 7.9% in third-generation Anaconda™ endografts over a median follow-up of 59 months, with 10.7% of patients treated outside the IFU. 23 This was associated with an increased risk of late failure including migration, probably due to lack of adequate sealing. 23 The authors did not relate treatment outside the IFU to limb occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year results of the French registry report 98.3% technical and 94.9% clinical success, but there have been concerns about a high limb occlusion rate. 7,8 There are unfortunately no large studies comparing gate cannulation with Anaconda TM to traditional methods, and the device is not commercially available in the US.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Midy et al 1 report five year outcomes for the third generation Anaconda stent graft system (Vascutek; Terumo, Paisley, UK) from a post-approval French multicentre prospective observational study.…”
mentioning
confidence: 99%